Property Damage and Exposure to Other People in Distress Differentially Predict Prosocial Behavior After a Natural Disaster. (April 2019) - Vardy, Tom; Atkinson, Quentin D.
The persistent threat of natural disasters and their attendant resource shocks has likely shaped our prosocial drives throughout human evolution. However, it remains unclear how specific experiences during these events might impact cooperative decision making. We conducted two waves of four modified dictator-game experiments with the same individuals in Vanuatu ( N = 164), before and after Cyclone Pam in 2015. After the cyclone, participants were generally less likely to show prosocial motives toward both in-group and out-group members and more likely to show parochialism when sharing between groups. Experiencing greater property damage predicted a general decrease in prosocial allocations and preference for participants' in-group. By contrast, exposure to other people in distress predicted increased prosocial allocations to both participants' in-group and out-groups. Our results suggest that people adjust their prosocial behavior in response to natural disasters but that the nature and direction of the effect depend on the type and severity of their experiences.